Generation Mean Analysis Reveals the Inheritance of Yield and its Components in Wide Compatible Elite indica Rice Restorer Line - Nanda, Kalpataru; Chakraborty, Nihar Ranjan; Nanda, Ashutosh; Arsode, Pandurang; Jena, Debarchana; Rout, Diptibala; Samantaray, Sanghamitra; Katara, Jawahar Lal; Verma, Ramlakhan (International Journal of Economic Plants, 2025)
The experiment was conducted during rabi (December-2021 to April-2022) at ICAR–National Rice Research Institute (NRRI), Cuttack, Odisha, India to unravel the genetic architecture underlying yield and its associated traits, generation mean analysis was conducted on six generations (P₁, P₂, F₁, F₂, B₁ and B₂) derived from a cross between two elite rice restorer lines, CR 1033 and CR 22-1-5-1. Results from the scaling tests indicated the presence of epistatic interactions across all studied traits, necessitating the application of a six-parameter model to dissect the generation means into additive, dominance, and interaction components. The inheritance of all evaluated traits was governed by a complex interplay of additive, dominance, and epistatic gene actions, with non-additive variance consistently surpassing additive or fixable variance components. For the majority of traits, dominance effects (h) emerged as the most influential gene effects, while (dominance×dominance) interactions (l) represented the predominant epistatic effects. Interestingly, several traits—including days to 50% flowering, days to maturity, plant height, grains panicle-1, yield plant-1, grain length, grain width, and the grain length-to-width ratio—displayed opposing signs for dominance effects (h) and (dominance×dominance) interactions (l), suggesting the involvement of duplicate epistasis in their genetic control. Consequently, selection for these traits may be more effective in later generations. Furthermore, bi-parental mating among superior segregants may help disrupt unfavorable linkages and facilitate the accumulation of desirable alleles. Traits such as plant height, grain width, and the grain length-to-width ratio exhibited significant negative heterobeltiosis, largely due to the subpar performance of F₁ hybrids relative to their parents.